High-level Chemoresistance in Paclitaxel-resistant C-33A Cells Involves the Alteration of Multiple Signaling Pathways and the Drug Efflux Phenotype by Modulating Coding and Long Non-coding RNAs - Martínez-Valenzuela, Marcela; L. Duriez-Tizoc, Nidia; Cisneros Hernández, Mireya; Bernal-Reynaga, Rodolfo; García-Gasca, Alejandra; R. Parra-Unda, Jesús; Peralta-Zaragoza, Oscar; F. Clemente-Soto, Aldo (Asian Pacific Journal of Cancer Biology, 2026)
Background: In chemoresistance, a variety of oncogenic signaling pathways can be activated and interconnected to combat drug toxicity, making anticancer pharmacological strategies complex. Objective: This study aimed to generate a paclitaxel-chemoresistant cancer cell line scaffold and explore its mechanisms of chemoresistance. Materials and methods: Total RNAs from C-33A and C-33A RPTX (paclitaxel-resistant) cells were sequenced to determine the transcriptome of coding and long non-coding RNAs (lncRNAs). Enrichment analysis of differentially expressed genes (DEGs) was conducted. Flow cytometry was performed to analyze doxorubicin accumulation in C-33A RPTX cells. Results: C33-A RPTX cells achieved a resistance index of 55. 1332 genes were differentially expressed (log2 fold-change>1). Gene ontology (GO) analysis revealed that biological processes, such as angiogenesis and mesenchymal development, were altered, while the mainly altered cellular components were from the extracellular matrix (ECM). Meanwhile, Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that signaling pathways, including PI3K/Akt, MAPK, Calcium, ECM-receptor, Rap1, EGFR tyrosine kinase inhibitor resistance, tight junction, and platinum drug resistance, were altered by coding RNAs or long non-coding RNAs (lncRNAs). Finally, the overexpression of the ABCB1 gene in C-33A RPTX cells correlated with a drug efflux phenotype, as evidenced by reduced cellular accumulation of the reporter drug doxorubicin. Alterations in signaling pathways recognized as relevant to chemoresistance and increased drug efflux, driven by changes in the expression patterns of coding RNAs and lncRNAs, may be cooperating to establish resistance to paclitaxel in C-33A RPTX cells. Conclusions: This C-33A RPTX model provides a new experimental platform to study the molecular mechanisms of chemoresistance in cervical cancer. The study integrates both coding and non-coding RNAs, revealing their coordinated alteration in chemoresistance-related signaling pathways. Thus, this dual-level analysis represents a novel systems-level insight into paclitaxel resistance. Beyond descriptive transcriptomics, this resistant model is proposed as a biological platform for testing novel antineoplastic compounds and exploring their mechanisms of action, giving it translational application.